Preparation of trade specialists at VU faculty of economics and their correspondence to market needs - Martinavičius, Jonas (Buhalterinės apskaitos teorija ir praktika, 2014)
This research is dedicated to analysing the development of preparation process of trade specialists at Vilnius University. Highest focus is laid on the period after the restoration of Lithuanian’s independence. Statistical analysis covering dynamics and scope of trade graduates from Trade faculty and later Economics faculty is performed. While revealing aims of study programmes and their achievement through development of generic and subject specific competencies, peculiarities of preparing trade specialists at bachelor and master levels are presented. Qualitative valuation of study programmes aimed at preparing trade specialists, their development and correspondence to market needs is performed employing massive survey data.
Keywords: trade specialists; Faculty of Economics; study programs; graduates; questionnaire survey; assessment of competences; satisfaction with studies; opinion of employers